2012
DOI: 10.1186/1476-4598-11-83
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of CD44 alternative splice pattern in the course of human colorectal adenocarcinoma progression

Abstract: BackgroundCD44 is considered as ‘a’ metastasis associated gene, despite the fact that it is an umbrella term for a group of molecules produced from a single gene by alternative splicing. However, little consideration is given to the above in the literature of colorectal carcinomas as well as other tumour types, leading to confusion and contradictory results about its possible role in tumour progression.MethodsWe compared the CD44 alternative splice pattern (ASP) of three genetically different human colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 58 publications
(41 reference statements)
5
47
0
1
Order By: Relevance
“…A similar finding was also observed in glioma mouse model suggesting the importance of CD44 in cancer stemness [8]. Some recent studies have exhibited CD44 as cancer stem cell marker in breast, gastric, pancreatic, colorectal and other cancers [9][10][11][12][13][14][15][16][17]. Different tumor types and their associated cells in the microenvironment express probably different sets of CD44 isoforms with a varied combination of variants.…”
Section: Role Of Cd44 In Cancer Proliferationsupporting
confidence: 72%
“…A similar finding was also observed in glioma mouse model suggesting the importance of CD44 in cancer stemness [8]. Some recent studies have exhibited CD44 as cancer stem cell marker in breast, gastric, pancreatic, colorectal and other cancers [9][10][11][12][13][14][15][16][17]. Different tumor types and their associated cells in the microenvironment express probably different sets of CD44 isoforms with a varied combination of variants.…”
Section: Role Of Cd44 In Cancer Proliferationsupporting
confidence: 72%
“…The expression of key proteins in the CD44, β-catenin, and FAK pathways, which play an important role in CRC metastasis [7]–[9] was analyzed next. We observed a gradual increase of high molecular weight CD44 expression observed at ∼150 kDa in HT29 LM cell lines, with maximum CD44 expression in HT29 LM3 compared to the parental HT29 cell line ( Figure 3A ) .…”
Section: Resultsmentioning
confidence: 99%
“…These discrepancies may be due to different patient material and follow up duration, antibodies, and immunohistochemical techniques used in different studies (2,9). Furthermore, a number of studies have demonstrated CD44 expression in most non-tumoral epithelial tissues, including stomach mucous membrane, small intestinal, prostate, ductal epithelium of breast, skin, hair follicles, and transitional epithelium (1, 2, 9).…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, colorectal cancer (CRC), or rather its progression to metastatic disease, accounts for 25% of tumor deaths (2). CRC evolves through a series of morphologically recognizable stages, known as the adenoma-carcinoma sequence.…”
Section: Introductionmentioning
confidence: 99%